2013
DOI: 10.1364/oe.21.002072
|View full text |Cite
|
Sign up to set email alerts
|

Third order nonlinear optical property of Bi_2Se_3

Abstract: The third order nonlinear optical property of Bi₂Se₃, a kind of topological insulator (TI), has been investigated under femto-second laser excitation. The open and closed aperture Z-scan measurements were used to unambiguously distinguish the real and imaginary part of the third order optical nonlinearity of the TI. When excited at 800 nm, the TI exhibits saturable absorption with a saturation intensity of 10.12 GW/cm² and a modulation depth of 61.2%, and a giant nonlinear refractive index of 10⁻¹⁴ m²/W, almos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
119
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 271 publications
(122 citation statements)
references
References 29 publications
2
119
1
Order By: Relevance
“…), [ 2 ] and topological insulators (Bi 2 Se 3 , Bi 2 Te 3 , etc.) [ 3 ] with outstanding electronic and optical properties [4][5][6][7][8] have been widely used in energy storage device, transistor, photodetectors, and electroluminescent devices. [9][10][11][12] Furthermore, some of these nanomaterials are also used as optical absorber for ultrafast photonics, such as passive Q-switcher, optical limiter, and mode locker, because of their broadband nonlinear optical response if under high power laser illumination.…”
Section: Introductionmentioning
confidence: 99%
“…), [ 2 ] and topological insulators (Bi 2 Se 3 , Bi 2 Te 3 , etc.) [ 3 ] with outstanding electronic and optical properties [4][5][6][7][8] have been widely used in energy storage device, transistor, photodetectors, and electroluminescent devices. [9][10][11][12] Furthermore, some of these nanomaterials are also used as optical absorber for ultrafast photonics, such as passive Q-switcher, optical limiter, and mode locker, because of their broadband nonlinear optical response if under high power laser illumination.…”
Section: Introductionmentioning
confidence: 99%
“…Shortly after that, Zhao et al presented the achievement of ultrashort pulse generation in the fibre laser mode locking by the TMD-based SA [33]. Further investigations with the Z-scan technique showed that the TMDs also possess large nonlinear refractive index [34]. Thus, the TMDs could serve as both the high nonlinear photonic device and the SA in the laser system.…”
Section: Introductionmentioning
confidence: 99%
“…Topological surface states are conducting, spin-locked, and protected by symmetry from backscattering by nonmagnetic impurities [10][11][12][13]. Bi 2 Se 3 is the prototypical TI (albeit doped in the asgrown samples), and has been intensively studied for its electronic, thermoelectric [14,15], and optical properties [16][17][18][19][20][21][22][23][24]. It has been proposed [25] that two-color injection currents can be injected by a laser pump and its second harmonic, and this was observed [26] in Bi 2 Se 3 thin films using a terahertz (THz) probe.…”
Section: Introductionmentioning
confidence: 99%